2017
DOI: 10.1155/2017/2314813
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Celiac Disease in Russia: Regional Data and Estimated Prevalence

Abstract: Celiac disease (CD) is an autoimmune enteropathy triggered by the ingestion of dietary gluten from some cereals mainly in individuals carrying the HLA-DQ2 and/or HLA-DQ8 haplotypes. As an autoimmune disease, CD is manifested in the small intestine in the form of a progressive and reversible inflammatory lesion due to immune response to self-antigens. Indeed, CD is one of the most challenging medicosocial problems in current gastroenterology. At present, the global CD prevalence is estimated at approximately 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…At present, the global CD prevalence is estimated at approximately 1% with a clear tendency to increase based on data from various locations [15-17]. This lifelong disorder should be identified promptly, but the availability of screening strategies for CD is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the global CD prevalence is estimated at approximately 1% with a clear tendency to increase based on data from various locations [15-17]. This lifelong disorder should be identified promptly, but the availability of screening strategies for CD is debatable.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from North Jordan also documented female predominance. Still, male predominance was reported in Pakistani children and in children in some areas of the Russian federation [ 9 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Savvateeva et al reported data on the polymorphic variants of HLA-DQA1 and -DQB1 genes in CD patients from the cities of Tomsk and Krasnodar (which are located in Russia, north and west of Kazakhstan respectively) and from Yakutia (Eastern Russia). These studies (all published in Russian) suggested that the allelic frequencies of CD-related HLA-DQ genes in those populations may be comparable to those observed in Europe [35].…”
Section: Central Asiamentioning
confidence: 95%
“…However, a paper by Savvateeva et al first provided an overview on CD in Russia and, interestingly, also cited some references of studies coming from the surrounding republics of Central Asia [35]. Therefore, some more information about CD in Central Asia could be obtained from Russian-language medical sources.…”
Section: Central Asiamentioning
confidence: 99%